The relationship between speed, strength and jumping abilities in elite junior handball players - Ingebrigtsen, J.; Jeffreys, I. (Serbian Journal of Sports Sciences, 2012)
The present study aimed to examine the relationship between strength (squat and bench press), jumping ability in countermovement (CMJ) and squat (SJ) jump, 10 m and 30 m sprint time and 6x30m repeated sprint ability (RSA) in a group of 29 male elite youth handball players aged 16.5±0.8 years, with stature of 184.3±4.8 cm and body mass of 77.0±9.4, who all voluntarily participated. Coefficients of correlation were determined and tested for significance by using the Pearson`s product-moment test. Firstly, sprint time results indicated a significant relationship with jumping height in absolute terms over 0-10 m and 0-30 m